2019
DOI: 10.1002/prot.25782
|View full text |Cite|
|
Sign up to set email alerts
|

Modification of lactoferrin by peroxynitrite reduces its antibacterial activity and changes protein structure

Abstract: Lactoferrin (LF) is a multifunctional protein that plays important physiological roles as one of the most concentrated proteins in many human and other mammalian fluids and tissues. In particular, LF provides antibacterial properties to human milk, saliva, and tear fluid. LF also protects against stress‐induced lipid peroxidation at inflammation sites through its iron‐binding ability. Previous studies have shown that LF can be efficiently nitrated via biologically relevant mediators such as peroxynitrite (ONOO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…is finding corroborates the literature, which cites the presence of the protein in question in the TF of humans [44], koalas [14], and dogs [14,52]. It is a multifunctional binding protein [29], produced by the acinar cells of the main and accessory lacrimal glands, with antimicrobial and anti-inflammatory action. erefore, it plays an important role in innate immunity and helps maintain ocular surface homeostasis [3,29].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…is finding corroborates the literature, which cites the presence of the protein in question in the TF of humans [44], koalas [14], and dogs [14,52]. It is a multifunctional binding protein [29], produced by the acinar cells of the main and accessory lacrimal glands, with antimicrobial and anti-inflammatory action. erefore, it plays an important role in innate immunity and helps maintain ocular surface homeostasis [3,29].…”
Section: Discussionsupporting
confidence: 90%
“…It is a multifunctional binding protein [29], produced by the acinar cells of the main and accessory lacrimal glands, with antimicrobial and anti-inflammatory action. erefore, it plays an important role in innate immunity and helps maintain ocular surface homeostasis [3,29]. Its antimicrobial action occurs because lactotransferrin inhibits the classical complement activation pathway and binds to free iron in tears, reducing the availability of iron required for bacterial growth [3,29,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as mentioned above, recent studies have reported that mastitis increases LF concentrations [ 27 , 50 ]. LF sequesters Fe 3+ , preventing the formation of hydroxyl radicals via the Fenton reaction, and in turn prevents lipid peroxidation [ 51 , 60 ]. Therefore, the increase in LF content in milk could also contribute to the decrease in MDA concentration observed in the mastitis group ( Figure 4 a,b).…”
Section: Discussionmentioning
confidence: 99%
“…At this time, it is proposed that the main cause, at least for protein modification, is related to the reactive nitrogen species (RNS) production. These species are generated when NO reacts with O 2 to form peroxynitrite (ONOO -), a strong oxidant, that easily reacts with nucleophilic molecules (Alhalwani et al, 2020). If the production of NO is increased, the steady state concentration of ONOOis also enhanced, and this situation could harm proteins via tyrosine (Tyr) nitration (Radi, 2018).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%